Childhood musculoskeletal impairment in Malawi from traumatic and non-traumatic causes: a population- based assessment using the key informant method - Linder, CL; Atijosan-Ayodele, O; Chokotho, L; Mulwafu, W; Tataryn, M; Polack, S; Kuper, H; Pandit, H; Lavy, C (BioMed Central, 2021)
Background Musculoskeletal impairment (MSI) in children is an under-recognised public health challenge. Although preventable, road injuries and other traumas continue to cause significant impairments to children worldwide. The study aimed to use the Key Informant Method (KIM) to assess prevalence and causes of MSI in children in two districts in Malawi, estimating the associated need for services provision, with a focus on traumatic aetiology. Methods The KIM was conducted in the districts of Thyolo (Southern Malawi) and Ntcheu (Central Malawi) in 2013. Five hundred key informants were trained to identify children who may have one of a range of MSI. The identified children were referred to a screening camp where they were examined by medical experts with standardised assessment protocols for diagnosing each form of impairment. Results 15,000 children were referred to screening camps. 7220 children were assessed (response rate 48%) for an impairment of whom 15.2% (1094) had an MSI. 13% of children developed MSI from trauma, while 54% had a neurological aetiology. For MSI of traumatic origin the most common body part affected was the elbow. Less than half of children with MSI (44.4%) were enrolled in school and none of these children attended schools with resources for disability. More than half of children with MSI (60%) had not received required services and 64% required further physical therapy. Conclusions The KIM method was used to identify a high prevalence of MSI among children in two districts of Malawi and estimates an unmet need for dedicated MSI services.